2022
DOI: 10.1186/s12943-022-01570-4
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA MTCL1 promotes advanced laryngeal squamous cell carcinoma progression by inhibiting C1QBP ubiquitin degradation and mediating beta-catenin activation

Abstract: Background Circular RNAs (circRNAs) are involved in regulatory processes of ubiquitination and deubiquitination in various tumors at post-transcriptional epigenetic modification level. However, the underlying mechanism and its biological functions of circRNAs in the advanced laryngeal squamous cell carcinoma (LSCC) remain obscure. Methods RNA sequencing and quantitative real-time PCR (qRT-PCR) assays were applied to screen for circRNAs differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…However, in terms of correlation analysis, our results showed that hsa_circ_0070512 only correlated circRNAs have been demonstrated to have a number of biological activities in previous investigations, including as binding proteins, acting as "molecular sponges" for miRNAs, and translating proteins as coding peptides. [24][25][26] Of these, circRNA has been most extensively investigated as a "molecular sponge" for miRNAs that regulate miRNA expression and thus participate in tumor progression. For example, hsa_circ_0003258 promotes PCa progression via miR-653-5p, 27 hsa_circ_0001955 promotes malignant metastasis of colorectal cancer cells via miR-583, 28 and circSTX6 promotes pancreatic ductal adenocarcinoma proliferation via miR-449b-5p.…”
Section: Discussionmentioning
confidence: 99%
“…However, in terms of correlation analysis, our results showed that hsa_circ_0070512 only correlated circRNAs have been demonstrated to have a number of biological activities in previous investigations, including as binding proteins, acting as "molecular sponges" for miRNAs, and translating proteins as coding peptides. [24][25][26] Of these, circRNA has been most extensively investigated as a "molecular sponge" for miRNAs that regulate miRNA expression and thus participate in tumor progression. For example, hsa_circ_0003258 promotes PCa progression via miR-653-5p, 27 hsa_circ_0001955 promotes malignant metastasis of colorectal cancer cells via miR-583, 28 and circSTX6 promotes pancreatic ductal adenocarcinoma proliferation via miR-449b-5p.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs have shown great potential as therapeutic molecular tools in many cancers such as HNSCC ( 110 , 166 , 167 ), breast cancer ( 168 ), hepatocellular carcinoma ( 169 ), papillary thyroid cancer ( 170 ) gastric cancer ( 171 ). Compared with existing linear miRNA antagonists, circRNAs are structurally more stable, more resistant to degradation by nucleases without chemical modification, and well tolerated in vivo ( 172 ).…”
Section: Discussionmentioning
confidence: 99%
“…When β-catenin enters the nucleus, some circRNAs interact with the genes downstream of the Wnt pathway. CircMTCL1 promotes advanced laryngeal squamous cell carcinoma progression by inhibiting C1QBP ubiquitin degradation and mediating β-catenin accumulation in the cytoplasm and nucleus 80 . In endometrial carcinoma, the hsa_circ_0002577/miR-197/CTNND1 axis affects the expression of β-catenin, cyclin D1, and c-Myc, thus activating the Wnt signaling pathway 81 .…”
Section: Multiple Signaling Pathways Of Circrnas In Cancersmentioning
confidence: 99%